The Authority of Class II Auction Officials Regarding the Legality of Auction Minutes in Relation to Legal Certainty - Firsta Vindy Ausely; Dita Perwitasari (NOVUM : JURNAL HUKUM, 2026)
Minister of Finance Regulation N umber 189/PMK.06/2017 authorizes Class II Auctioner to conduct sales of goods through voluntary non-execution auctions and prepare minutes of the event known as “minutes of auction”. The limited explanation of Article 15 paragraph (2) letter g of the Law on Notary Position Amendment (UUJN-P), regarding notaries being appointed as Class II Auctioneer to exercise similar authority, creates normative ambiguity that causes legal uncertainty. This study aims to examine the legal certainty of the authority of the Class II Auctioneer on the legality of the minutes of the auction and the form of responsibility if there are problems with the minutes of the auction. Th e research method use d is normative legal research method using a statutory approach and conceptual approach. The results showed that Class II Auction eer has the capacity to make minutes of auction prepared in accordance with the provisions of Article 1868 of the Civil Code. Based on the analysis of the explanation of the UUJN-P article, notaries must follow the requirements and procedures for the appointment of Class II Auctioneer and do not require applicants to have a notary background. The Class II Auction eer is fully responsible for the formal and material correctness of the minutes of auction prepared. If there are editorial errors, corrections can be made through the procedures specified in the Ministry of Finance Regulation Number 86 of 2024 concerning Minutes of Auction, as a form of administrative responsibility of the official concerned.